Local government in Portugal in times of pandemics: website communications and democratic legitimacy - Almeida, Maria Antónia (ECPR General Conference 2021, 2021)
How is local government in Portugal managing its image? How are municipalities behaving regarding transparency? How much information are municipalities displaying in their websites and what are their contents? Are local representatives using this tool for their citizens’ best interest? Is the Covid-19 pandemic a test of municipal governments’ levels of transparency and/or a stimulus for its further development? In order to answer these questions, our methodology included researching other studies on transparency in the Portuguese local government and then checking the amount of information displayed on municipalities’ websites and its contents. There was a pre-existing database with all 308 municipalities which had been used to analyse attraction strategies for people and companies, as well as central government policies for the interior regions. In face of the Covid-19 pandemic and the emergency state, a sampling of 17 municipal websites was randomly chosen from this database and new information was collected focusing on mayors’ messages, health and sanitary procedures, and municipal actions during confinement. The purpose of this research was to study how Portuguese municipalities are working to enhance democratic legitimacy. One important aspect is to establish the levels of transparency and the quality of the information provided by Portuguese municipalities, particularly during the Covid-19 pandemic. With this new and original approach on public image and content analysis, the main findings reveal that many local representatives, particularly in large municipalities, are concerned with image, transparency and with exploiting new ways of improving local democracy Some case studies reveal dynamic mayors and councillors. However, only a few websites provide complete information. This research limitation shows some lack of interest in modernising and moving forward with the quality of local government in Portugal.